Make a feminist out of you: Disney´s potential to promote behavioural change in gender stereotyping - Silva, Inês Soares da Costa Cardoso da (2021)
Disney is a culturally powerful brand, whose products largely shape behaviour, namely children’s behaviour (Coyne, Linder, Rasmussen, Nelson & Birkbeck, 2016), making it essential to critically examine the brand’s impact at various levels. Hence, this dissertation aims to understand the potential of Disney films to effectively promote behavioural change regarding gender stereotyping in society. Designed as a case study, this research uses thematic analysis (Braun & Clarke, 2006) to identify and analyse the gender messages present on Disney’s two adaptations of the Chinese legendary folk poem “The Ballad of Mulan” – Mulan (Bancroft & Cook, 1998) and Mulan (Caro, 2020). Focusing on Disney films and their potential to facilitate behavioural change, this study frames them as possible products of social marketing campaigns in the light of Fox and Kotler’s (1980) argument of product development as a medium to increase the success of social marketing strategies. Results show that the two version of the Mulan convey contrasting views of women in society, patent on the noticeable more feminist tone of the live-action remake. Overall, Disney’s new product strategy seems promising for more equitable portrayals of gender in cinema, as long as the studios ensure that all gender messages conveyed in the films reflect progressive tone to prevent latent reinforcement of patriarchal ideals.